Evaluation of processed cheese viscoelastic properties during sterilization observed in situ - Buňka, F; Sedlačík, M; Foltin, P; Lazárková, Z; Pětová, M; Buňková, L; Purevdorj, K; Talár, J; Kůrová, V; Novotný, M; Vlkovský, M; Salek, R N (Journal of dairy science, 2023)
Sterilized processed cheese is a specific dairy product with a prolonged shelf life intended for regular retail offer but also as food provisions for armies during peacetime, as well as during crisis and emergency situations, and for storage in state material reserves. Storage requirements are usually defined as ≤25°C for at least 24 mo. One of the ways to achieve such a shelf life is sterilization. Therefore, the aim of the work was to describe, for the first time in the available scientific literature, in situ changes in the viscoelastic properties of spreadable melt (34% wt/wt DM content, 45% wt/wt fat in DM content, and 14% wt/wt protein content) during an increase in temperature (target temperature 122°C), holding at sterilization temperature (20 min) and subsequent cooling (to ~30°C). While increasing to the target sterilization temperature, a significant decrease occurred in the storage and loss moduli values. Both moduli started to increase again during the target sterilization temperature period and during the whole cooling phase. The values of the storage and loss moduli were significantly higher at the end of the cooling of the sterilized product, and conversely, the phase angle value was lower compared with the melt before sterilization. As a result of sterilization, an increase occurred in the levels of markers of the Maillard reaction complex and lipid oxidation processes. The value of hardness, corrected stress, and elongational viscosity also increased compared with nonsterilized products. As a result of sterilization, the flavor worsened and sterilized processed cheeses showed darker (brownish) color. However, even after sterilization, the products were evaluated as acceptable for consumers and maintained their spreadability.
Keywords: Food Handling; Temperature; Cheese; processed cheese; sterilizace; in situ study; Maillardova reakce; rheology; sýr; Sterilization; Animals; nízká teplota; zvířata; Cold Temperature; Maillard Reaction; manipulace s potravinami; teplota; heating; sterilization